Xochiquetzallia magnifolia (Asparagaceae, Brodiaeoideae), a new species from Oaxaca, Mexico - García-Mendoza, Abisaí Josué; Gutiérrez, Jorge (Phytotaxa, 2022)
A recent exploration in Mixteca Alta, state of Oaxaca, and the morphological review of herbarium specimens allowed the identification of a new species of Xochiquetzallia, genus recently segregated from the paraphyletic Dandya. The objective of this work is to describe and illustrate Xochiquetzallia magnifolia, which can be recognized by its leaf size, scape, floral morphology, number of flowers per umbel, and inclined style. Due to its limited occurrence area and known distribution in one locality, it is considered vulnerable (VU) according to the guidelines of the International Union for Conservation of Nature (IUCN).